Dechema chemistry data series : liquid - liquid equilibrium data collection 4 supplement 1 - Macedo, E. A.; Rasmussen, P. (Frankfurt Dechema, 1987)
part 4
Tables, diagrams and model parameters for binary ternary and quaternary systems
Keywords: Liquid - Liquid Equilibrium